Normal values of the electrocardiogram in Angolans - Gonçalves, Mauer (2021)
Introduction: Studies on the normal electrocardiogram limits in African populations are limited, especially in sub-Saharan Africa. There is no literature describing normal ECG limits in Angolans. Objectives: The aim of this study is to establish the normal ECG values for adult Angolans, without established heart disease, stratified by gender and age.